An Online Survey of Public Knowledge, Attitudes, and Perceptions Toward Whales and Dolphins, and Their Conservation - Naylor, Whitney; Parsons, E. C. M. (Frontiers in Marine Science, 2018)
In 2015, an online survey was conducted to investigate public attitudes and perceptions toward key cetacean (whale, dolphin, and porpoise) conservation and 'hot topic' issues such as legislative protection and whaling (n=858). The vast majority of the participants in this study indicated their permanent residence was the United States (n=577) or India (n=251). Perceptions of participants on the conservation priority of cetacean species did not match with the factual IUCN status, where most participants assumed that the larger and more charismatic whales (blue whale, 24.01%; humpback whale, 22.14%; and killer whale, 23.43%) were more endangered or more important to conserve than the small cetacean species such as the Vaquita or Hector's dolphin. Additionally, 39.74% of participants indicated the bottlenose dolphin was the most important to conserve. More members of the public highlighted non-existent (fake) species (e.g. pygmy short-fined whale, lump-headed dolphin, and majestic spotted dolphin) as being of conservation concern than certain species of actual genuine concern. The majority of participants considered dolphins and whales to be "under protected" or only "slightly protected" (29.95%; 41.96%, respectively) and expressed that marine mammal conservation laws and policies were "very important" or "important" (47.43%; and 37.88%, respectively). In addition, 86.83% of participants expressed opposition to the hunting of dolphins and whales (57.93% "strongly opposed" and 28.90% "opposed"); however, only 47.44% of participants were aware that several countries are still involved in whaling. A lack of awareness of the conservation status of whales and dolphins and continued whaling activities suggests that greater outreach to the public about the conservation status of whale and dolphin species is needed.